Mass migration and climate change: Dermatologic manifestations - Ruby Kwak, BS; Kanika Kamal, BA; Alexandra Charrow, MD, MBE; Saami Khalifian, MD (Wolters Kluwer, 2021)
Major changes in climate resulting in mass migrations have unique dermatologic implications for global vulnerable populations. Dermatologic manifestations commonly accompany the infectious and communicable diseases that proliferate in the settings of confinement, crowding, and limited sanitation associated with mass migration. Ectoparasitic infestations abound in refugee camps, and poor nutrition, hygiene, and compromised immunity put refugees at an increased risk for more dangerous infectious diseases carried by these ectoparasites. Climate change also profoundly affects the worldwide distribution of various vector-borne illnesses, thereby leading to the emergence of various communicable diseases in previously nonendemic areas. Natural disasters not only disrupt important lifesaving treatments, but also challenge various infectious disease control measures that are critical in preventing rapid transmission of highly infectious diseases. This article reviews the infectious diseases commonly found in these scenarios and provides an in-depth discussion of important implications for the dermatologist.